2022
DOI: 10.3390/su14095507
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Sustainable Destinations: Empirical Evidence from Selected Mediterranean Countries

Abstract: Within the globalized tourism market, tourism destinations have the option to turn to sustainability as a conceptual and management framework for their unique branding and identity proposition. This research highlights the importance and utility of sustainability branding that stems from clustering tourism destinations based on the similarities of their tourism performance attributes. The study builds on secondary data from 11 coastal destinations in 8 Mediterranean countries. The analysis leads to the formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A destination's internationalization is important as it creates opportunities for foreign income flows to the destination's economy, as well as information and knowledge sharing, improvements of the destination's reputation, low dependency on domestic tourism sources, and high levels of overall sustainability [29]. Glyptou et al [17] proceed to a cluster analysis of performance rankings of Mediterranean destinations, concluding that sustain-able destinations are characterized by high economic and social performance combined with a low environmental footprint.…”
Section: Sustainability and Tourism Destinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A destination's internationalization is important as it creates opportunities for foreign income flows to the destination's economy, as well as information and knowledge sharing, improvements of the destination's reputation, low dependency on domestic tourism sources, and high levels of overall sustainability [29]. Glyptou et al [17] proceed to a cluster analysis of performance rankings of Mediterranean destinations, concluding that sustain-able destinations are characterized by high economic and social performance combined with a low environmental footprint.…”
Section: Sustainability and Tourism Destinationsmentioning
confidence: 99%
“…However, there seem to be no studies-at least according to authors' knowledge-that examine the impact of travel influencers in sustainable destinations. This would be interesting as these destinations offer many advantages of economic and social development with a low environmental burden and are constantly multiplying and present a growing interest [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ward clustering method was most relevant in segmenting respondents and performed significantly better than the other clustering methods used in the study. Other studies have also found Ward's method to be a useful clustering method for segmenting sustainable destinations [107,108].…”
Section: Main Conclusionmentioning
confidence: 99%
“…Several brand elements also have been evaluated to provide the basis for destination organizations to create a strategic destination brand by considering a supply and demand perspective (TASCI -GARTNER 2009). Nowadays, tourism destinations often utilize branding to provide a unique identity related to sustainability value (GLYPTOU et al 2022, LŐRINCZ et al 2021, CSAPÓ, J. -TRÓCSÁNYI, A.…”
Section: Introductionmentioning
confidence: 99%